Quantitative analysis of both lacrimal glands in unilateral primary acquired nasolacrimal duct obstruction, based on three-dimensional fast spin echo-Cube-Flex. Issue 156 (November 2022) - Zhao, Yali; Tian, Meng; Luo, Ban; Liang, Weiqiang; Wu, Hongyu; Wang, Qiuxia; Zhang, Jing
Abstract: Objective: To investigate whether unilateral primary acquired nasolacrimal duct obstruction (PANDO) changes the volume and water fraction of both lacrimal glands, using three-dimensional fast spin echo (3D-FSE)-Cube-Flex images, and to identify whether the lacrimal gland is a target organ in this disease. Methods: 3D-FSE-Cube-Flex images of both lacrimal glands in 25 healthy volunteers and 31 patients with unilateral PANDO were retrospectively reviewed. The differences in volume and water content in the lacrimal glands between the controls, non-PANDO side, and PANDO side groups were examined. Moreover, the associations between magnetic resonance imaging (MRI) parameters and disease duration were assessed with correlation analysis. Results: The lacrimal gland volumes were not significantly different between the PANDO and non-PANDO side groups, compared to the control group ( P = 0.484). However, the gland volumes tended to be increased bilaterally in patients with PANDO. In contrast, the gland water fractions in the PANDO and non-PANDO side groups were significantly higher than those in the control group ( P = 0.009 and P = 0.014, respectively), and similar between the non-PANDO and PANDO side groups ( P = 0.897). No correlation was found between the disease duration and the gland MRI parameters (volume and water fraction). Conclusions: Both lacrimal glands are affected by unilateral PANDO. A change in the water fraction of these glands appears to precede the change in volume and may be a sensitive early indicator.